Homoeopathic Treatment of Postnatal Stage IV Pressure Ulcer: A Case Report - Singh, Namrata; Das, Kapil (Homœopathic Links, 2023)
Pressure ulcer or decubitus ulcer is generally caused due to constant pressure on the dependent parts of the body owing to impaired blood circulation. Due to this condition, the affected area shows varying changes from disruption of normal skin texture to formation of ulcer, many a times with discharge. Very commonly seen in cases with restricted ambulatory functions and /or immunodeficiency, pressure ulcers become a nuisance if left unattended. A case of a 28-year-old female patient presented with stage IV decubitus ulcers on her right gluteal region since the delivery of her 6 month old child. She had complaints of stinging or splinter like pain and itching of affected area with discharge of offensive pus worsening at night and with slightest touch. On the basis of totality, Acidum nitricum 200 was given, which provided a very favourable result in terms of healing the ulcer and progressing the state to a healthier one within 3 months. The outcome assessment in this case report was done by using the ‘MONARCH Inventory’.
Keywords: decubitus ulcer; pressure ulcer; homoeopathy; MONARCH; Acidum nitricum; case report